Packaging and storage conditions to extend the shelf life of semi-dried artichoke hearts. (October 2016) - Sergio, L.; Gatto, M.A.; Spremulli, L.; Pieralice, M.; Linsalata, V.; Di Venere, D.
Abstract: Consumer interest in quick yet healthy food is increasing and the "ready-to-use" artichoke is a tasty, easy, food to prepare with excellent nutraceutical qualities. This study evaluated the postharvest performance of semi-dried artichoke (SDA) hearts. The product was packaged in air, in modified atmosphere (MA), and in vacuum and stored at 4 °C for 40 days. Sensorial, physical, biochemical, and microbiological parameters were evaluated during that period. The results show that storage in the absence of O2 and in the presence of a high CO2 percentage (30%) was the most effective method for preserving phytochemical content, antioxidant capacity, and hygienic traits and that SDA packaged in MA could be stored for more than 30 days. To our knowledge, this is the first time that the postharvest performance of SDA has been studied. The results indicate that this innovative product could have great market value due to the possibility of preserving its qualitative and sensorial proprieties in refrigerated conditions for long periods of time. Highlights: The postharvest performance of semi-dried artichoke hearts was evaluated. Sensorial, physical, biochemical and microbiological parameters were evaluated. Modified atmosphere (30% CO2  + 70% N2 ) packaging preserves more than air and vacuum. The product in modified atmosphere can be stored for more than 30 days a 4 °C.